THE EFFECT OF ONLINE LEARNING ON INTEREST IN LEARNING MATHEMATICS IN ELEMENTARY SCHOOLS - Nadisa Dwi Gunawan; Yudhie Suchyadi; Sumardi Sumardi (Journal of Social Studies Arts and Humanities (JSSAH), 2022)
This research is quantitative research with a causal approach. The purpose of this study is to find out the effect of online learning on interest in learning mathematics in grade IV at elementary school (SD Negeri 01 Pasir Muncang). Research data for the two variables in this study were obtained using a questionnaire instrument. Test the validity of the parent tutoring instrument using the Pearson Product Moment Correlation formula and the mathematics learning outcomes instrument using the Biseral Correlation Coefficient formula. Test the reliability of online learning instruments and interest in learning mathematics using the Alpha Cronbach formula. The population in this study were fourth grade students at elementary school (SD Negeri 01 Pasir Muncang), totaling 88 students. The samples taken were 47 students obtained using the Taro Yamane formula. Testing Prerequisite analysis in the form of normality test (Liliefors). After the normality test, homogeneity testing (Fisher) was then carried out. Data that has been declared normal and homogeneous is used to test the hypothesis whose results show that there is an effect of online learning on interest in learning mathematics. The simple correlation regression analysis technique produces a relationship model which is expressed in the form of a regression equation, namely Å¶ = 15.90 + 0.89X. This can be seen from the calculation results tcount (13.24) is greater than ttable (1.72), thus tcount (13.24) ttable (1.72) which means the correlation coefficient of online learning with interest in learning mathematics stated to be significant, this shows that there is an influence between online learning and interest in learning mathematics at elementary school.